1990
DOI: 10.1007/bf00196235
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic disturbance associated with mosaic aneuploidies

Abstract: The association of various unsystematic aneuploidies with premature centromere division (PCD) was observed in a patient with conspicuous clinical features and combined immunodeficiency. Trisomies and monosomies of almost all autosomes and gonosomal aberrations were found separately or in combination in a majority of the proband's lymphocytes and fibroblasts. The chromosome number varied from 44 to 50. A high proportion of the metaphases showed PCD or had the appearance of C-anaphases. These findings probably r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…A "generalized" PCD affecting all the chromosomes has been found in four healthy individuals of three gener- (Madan et al 1987), in families with a history of spontaneous abortions (Murthy and Prabhakara 1990;Rudd et al 1983), in subfertile families (Gabarron et al 1986;Rudd et al 1983), in a patient with ambiguous genitalia (Miller et al 1990) and in male pseudohermaphroditism (Rangnekar et al 1990). Some of these patients probably had "C-anaphases" as described by Chamla et al (1980) and Chamla (1988a, b).…”
Section: Discussionmentioning
confidence: 96%
“…A "generalized" PCD affecting all the chromosomes has been found in four healthy individuals of three gener- (Madan et al 1987), in families with a history of spontaneous abortions (Murthy and Prabhakara 1990;Rudd et al 1983), in subfertile families (Gabarron et al 1986;Rudd et al 1983), in a patient with ambiguous genitalia (Miller et al 1990) and in male pseudohermaphroditism (Rangnekar et al 1990). Some of these patients probably had "C-anaphases" as described by Chamla et al (1980) and Chamla (1988a, b).…”
Section: Discussionmentioning
confidence: 96%
“…Since the multiple congenital anomalies/mental retardation syndrome associated with this cytogenetic phenomenon was first reported by Scheres et al (1986), to date, only several patients have been reported (Tolmie et al 1988;Papi et al 1989;Miller et al 1990;Warburton et al 1991;Limwongse et al 1997;Nash et al 1997;Flejter et al 1998;Kajii et al 1998). Clinical features in the reported patients were variable, but growth retardation and microcephaly were frequently described.…”
Section: Introductionmentioning
confidence: 96%
“…In some patients, premature centromere division (PCD) was associated with numerical aneuploidies (Scheres et al 1986;Miller et al 1990;Warburton et al 1991;Limwonge et al 1997;Kajii et al 1998). PCD is a cytogenetic phenomenon characterized by parallel separated rod-like sister chromatids in metaphase.…”
Section: Introductionmentioning
confidence: 99%
“…PCD-related MVA has been reported in association with cancer and a clinical phenotype of microcephaly, central nervous system (CNS) anomalies, *Correspondence to: Chih-Ping Chen, Department of Obstetrics and Gynecology, Mackay Memorial Hospital, 92, Section 2, Chung-Shan North Road Taipei, Taiwan, Republic of China. Email: cpc mmh@yahoo.com mental retardation, pre-and postnatal growth restriction, a flat and broad nasal bridge, low-set ears, eye and skin abnormalities, and ambiguous genitalia in male patients (Scheres et al, 1986;Miller et al, 1990;Warburton et al, 1991;Kajii et al, 1998;Kawame et al, 1999;Limwongse et al, 1999;D'Agostino et al, 2000;Matsuura et al, 2000;Kajii et al, 2001;Jacquemont et al, 2002;Plaja et al, 2001aPlaja et al, ,b, 2003. Parental PCD and recurrence of PCD-related MVA in offspring have been described in several families (Kajii et al, 2001;Plaja et al, 2003).…”
Section: Introductionmentioning
confidence: 99%